Dalit Aesthetics and Consciousness in Sharad Poudel’s Likhe - Charmakar, Rudra Bahadur (Pursuits: A Journal of English Studies, 2022)
Dalit art and literature has been an inseparable part of Dalit movements in Nepal. It has its own aesthetic characteristics, literary features, paradigms and missions for Dalits’ rights, equality, dignity, and social transformation. However, there is no remarkable qualitative research focusing on Dalit aesthetic perspectives. This research article aims to explore the caste system, social context and consciousness in Dalit literature. It examines the literary paradigms and Dalit aesthetics characteristics and values in literature. For this purpose, the study has employed the emerging concept of Dalit aesthetics and consciousness as a theoretical lens developed by Sharankumar Limbale, C. B. Bharti, Arjun Dangle, Rajarao Dunna and Anju Bala to the novel "Likhe". The study has adopted the exploratory method with a qualitative approach. Findings of the study illustrate that Dalit literature has its own aesthetics features and values and literary paradigms. As a protest literature by its nature, Dalit literature awakens Dalits and backward communities to move against all types of atrocities, caste discrimination, oppression, exploitation. The study further elucidates that the novel "Likhe" portrays the Nepali society and the misery of Dalits. It delivers socio-political messages to establish an equity-based prosperous society through its context, content, plots and characters.